Quality of life in patients with HBV infection: a systematic review and meta-analysis - Fu,M; Lambert,G; Cook,A; Ndow,G; Haddadin,Y; Shimakawa,Y; Hallett,TB; Harvala,H; Sicuri,E; Lemoine,M; Nayagam,AS (JHEP Reports, 2025)
Background & AimsDespite nearly 250 million people worldwide estimated to have chronic hepatitis B virus (HBV) infection, health-related quality of life (HRQOL) in HBV-related disease has not been well characterised. We aimed to summarise existing data on HBV-related HRQOL and quantify summary utility values by stage of disease.MethodsEmbase, Global Health, PubMed, and Web of Science were searched for articles investigating HBV HRQOL. Meta-analyses for utility scores were pooled by stage of disease and utility instrument; meta-regression was further adjusted for the effect of current health expenditure as a percentage of gross domestic product (CHE/GDP) as a proxy of the importance of healthcare perceived by different countries.ResultsTwenty-two articles from nineteen studies, comprising 10,311 patients, were included. 74% of studies were performed in the Western Pacific Region, and 47% used the EuroQoL-5D-3L instrument. HRQOL was found to decrease with advancing stages of HBV-related disease. Meta-regression showed the following predicted mean utility scores for the different stages of chronic HBV infection: non-cirrhotic 0.842, compensated cirrhosis 0.820 (p=0.474 compared to non-cirrhotic), decompensated cirrhosis 0.722 (p=0.001) and hepatocellular carcinoma 0.749 (p=0.008). The type of tool used affected HRQOL and studies in populations where there was a higher CHE/GDP were associated with higher predicted utility values.ConclusionsChronic HBV infection impairs patients' HRQOL, even when there is no evidence of cirrhosis, and HRQOL is particularly impaired in the advanced stages of decompensated cirrhosis and hepatocellular carcinoma. These results have important implications for global hepatitis elimination efforts and are useful for economic analyses. However, further research is needed, particularly in high-burden, low-income settings where data is lacking.Impact and ImplicationsThis study's findings from 22 articles and 10,311 patients contribute to the